165k views
5 votes
4(x + 3) – 4 = 8(x+1)
What is x

User SnNaCk
by
5.7k points

2 Answers

5 votes

Answer:

x = 0

Explanation:

4(x+3) - 4 = 8(x+1)

Step 1. First, we distribute within the parenthesis.

4x + 12 - 4 = 8x + 8

Step 2. Then, we combine like terms.

4x + 8 = 8x + 8

Step 3. Then, move the coefficients to one side of the equation.

8 = 4x +8

Step 4. Move the constants to the other side of the equation.

0 = 4x

Step 5. Divide both sides by 4.

0 = x

User Adamasan
by
6.1k points
3 votes

Answer:

x = 0

Explanation:

Step 1: Simplify both sides of the equation.

4(x+3)−4=8(x+1)

(4)(x)+(4)(3)+−4=(8)(x)+(8)(1) (Distribute)

4x+12+−4=8x+8

(4x)+(12+−4)=8x+8 (Combine Like Terms)

4x+8=8x+8

4x+8=8x+8

Step 2: Subtract 8x from both sides.

4x+8−8x=8x+8−8x

−4x+8=8

Step 3: Subtract 8 from both sides.

−4x+8−8=8−8

−4x=0

Step 4: Divide both sides by -4.

−4x /−4 = 0 /−4

User Elchin
by
5.7k points